Effectiveness of a SARS-CoV-2 infection prevention model in elective surgery patients – a prospective study: does universal screening make sense?. (September 2021) - Moreno-Pérez, O.; Merino, E.; Chico-Sánchez, P.; Gras-Valentí, P.; Sánchez-Payá, J.
Summary: This observational study included patients who underwent pre-operative coronavirus disease 2019 (COVID-19) screening in order to preserve patient safety. Reverse transcriptase polymerase chain reaction (PCR) for severe acute respiratory syndrome coronavirus-2 was performed in 2292 of 8740 surgical procedures, and the incidence of a positive PCR result was 0.0022%. No healthcare-associated infections were detected. There was no difference in overall mortality or length of hospital stay compared with the same period from the previous year. A selective screening strategy to identify patients for PCR testing, based on isolation measures, presurgical clinical-epidemiological assessment and selected major surgeries susceptible to a poor COVID-19-related outcome, is effective and safe for patients and healthcare workers.